TECTONIC PROCESSES AND CRUSTAL EVOLUTION ON/OFFSHORE WESTERN PELOPONNESE DERIVED FROM ACTIVE AND PASSIVE SEISMICS - Papoulia, J.; Makris, J. (Bulletin of the Geological Society of Greece, 2010)
We developed velocity models of the crust and sediments offshore south western Greece, between the island of Zakynthos and Messinia. Using these velocity models and depth migrating the seismic data we delineated the main faults and associated them with the tectonic processes of western Greece. This active seismic experiment was essential for defining the limits between the continental domain of western Greece and the oceanic one of the deep Ionian Sea. We successfully linked the onshore with the offshore tectonics and for the first time it was possible to understand how the main dextral fault systems of Cephalonia and Andravida are responsible for the crustal deformation, and its link to the local seismicity. Most of the seismic activity is connected to thrusting, due to crustal shortening or strike-slip faulting that follows the two main dextral wrench faults of Cephalonia and Andravida. It was recognized that the back stop offshore western Peloponnese is floored by thinned continental crust of Preapulia and that the Hellenic Alpine napes do not extend in the back stop domain.